2010
DOI: 10.1186/1471-2334-10-192
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial migration through punctured surgical gloves under real surgical conditions

Abstract: BackgroundThe aim of this study was to confirm recent results from a previous study focussing on the development of a method to measure the bacterial translocation through puncture holes in surgical gloves under real surgical conditions.MethodsAn established method was applied to detect bacterial migration from the operating site through the punctured glove. Biogel™ double-gloving surgical gloves were used during visceral surgeries over a 6-month period. A modified Gaschen-bag method was used to retrieve organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 17 publications
0
45
0
16
Order By: Relevance
“…One explanation would be the increase of surgical team fatigue over time that can lead to inattention (22) . The frequent exchange of surgical gloves in longer procedures have been related to the reduction of microbial contamination rate (23)(24) , the replacement thereof being suggested during prolonged surgeries, preferably every 90 minutes (25) . The protocol of the study institution recommends that in a surgery with prosthesis implantation or duration above 3 hours the gloves should be replaced in the second hour or at different stages of the procedure, such as incision and preparation of the site of the prosthesis/implant, prosthesis placement and closure.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation would be the increase of surgical team fatigue over time that can lead to inattention (22) . The frequent exchange of surgical gloves in longer procedures have been related to the reduction of microbial contamination rate (23)(24) , the replacement thereof being suggested during prolonged surgeries, preferably every 90 minutes (25) . The protocol of the study institution recommends that in a surgery with prosthesis implantation or duration above 3 hours the gloves should be replaced in the second hour or at different stages of the procedure, such as incision and preparation of the site of the prosthesis/implant, prosthesis placement and closure.…”
Section: Discussionmentioning
confidence: 99%
“…Gloves have been known to be one of the important components of PPE and, along with hand hygiene, play a significant role in the prevention of HAI. Intact surgical gloves are an important barrier for transmission of infection to and from the patients [3]. Esteban et al demonstrated the possibility of transmission of hepatitis C from surgeon to the patients due to intraoperative perforation of the gloves [4].…”
Section: Discussionmentioning
confidence: 99%
“…It should therefore be recommended to repeat the scrub or rub procedure depending on duration of the surgical procedure [75]. In addition, it must be emphasised that surgical gloves do not provide absolute protection against contaminants [76]. Especially in trauma and orthopaedic surgery, unnoticed perforations are common, with perforation rates between 3.6% and 21%.…”
Section: Operative Environmentmentioning
confidence: 99%